Front Cover: Multiplexed Covalent Patterns on Double‐Reactive Porous Coating (Chem. Asian J. 11/2022). Issue 11 (27th April 2022) - Das, Supriya; Kumar, Ravi; Yang, Bingquan; Bag, Sudipta; Sauter, Eric; Hussain, Navid; Hirtz, Michael; Manna, Uttam
Abstract : Patterning double‐reactive porous coatings : A substrate‐independent porous dip coating with dual chemical reactivity enables multiplexed bulk‐infused and unclonable micropatterns of fluorophores attaching by distinct reaction pathways. The hydrophobicity of the coating restricts spreading of aqueous inks and enables miniaturization of patterns with high feature density. The resulting multiplexed micropatterns allow orthogonally readout and remain readable even after surface abrasion. More information can be found in the Research Article by Uttam Manna, Michael Hirtz et al.